Breaking down lignin in gamma-valerolactone: advances into a bioelectrorefinery - Lucie M. Lindenbeck; Sira Dahlhaus; Luca M. Wende; Björn B. Beele; Marcella Frauscher; Nils Helge Schebb; Christian W. Lehmann; Julia Bornhorst; Adam Slabon; Bruno V. M. Rodrigues (Green Chemistry Letters and Reviews, 2024)
This study builds upon our experience with electrocatalyzed dearomatization of lignin in aqueous systems, which has shown to produce sodium levulinate, sodium 4-hydroxyvalerate, sodium acetate, and sodium formate as major products. Here, we extend this investigation by exploring a water/γ-valerolactone (GVL) solvent system for electrochemical depolymerization and dearomatization of lignin, using Na2CO3 as electrolyte. GVL, derived from biomass, has frequently been employed for biomass treatment, notably in the Organosolv process. Consequently, various biorefinery strategies have emerged utilizing GVL as a green platform, primarily for its potential in delignifying lignocellulosic biomass when combined with water and dilute acid. This study proposes electrochemical depolymerization of lignin in GVL as a step toward the concept of a bioelectrorefinery, aiming to convert lignin into aliphatic organic chemicals. Consistent with our prior work in aqueous systems, applying a current of −100 mA over 8 h yielded sodium levulinate, sodium 4-hydroxyvalerate, sodium acetate, and sodium formate. Confirmation was provided by liquid chromatography electrospray ionization high-resolution mass spectrometry, nuclear magnetic resonance, and infrared spectroscopy. These findings advance our understanding of GVL as a biomass-based platform, highlighting its potential not only for biomass treatment but also as a medium for converting lignin into valuable aliphatic chemicals.